Antimicrobial Resistance in Bacterial Pathogens and Detection of Carbapenemases in Klebsiella pneumoniae Isolates from Hospital Wastewater - Hercules Sakkas; Petros Bozidis; Afrodite Ilia; George Mpekoulis; Chrissanthy Papadopoulou (MDPI AG, 2019)
During a six-month period (October 2017−March 2018), the prevalence and susceptibility of important pathogenic bacteria isolated from 12 hospital raw sewage samples in North Western Greece was investigated. The samples were analyzed for methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), extended-spectrum beta-lactamase (ESBL) producing Escherichia coli, carbapenemase-producing Klebsiella pneumoniae (CKP), and multidrug-resistant Pseudomonas aeruginosa. Antimicrobial susceptibility testing was performed using the agar diffusion method according to the recommendations of the Clinical and Laboratory Standards Institute. The diversity of carbapenemases harboring K. pneumoniae was examined by two phenotyping screening methods (modified Hodge test and combined disk test), a new immunochromatographic rapid assay (RESIST-4 O.K.N.V.) and a polymerase chain reaction (PCR). The results demonstrated the prevalence of MRSA, vancomycin-resistant Staphylococcus aureus (VRSA), VRE, and CKP in the examined hospital raw sewage samples. In addition, the aforementioned methods which are currently used in clinical laboratories for the rapid identification and detection of resistant bacteria and genes, performed sufficiently to provide reliable results in terms of accuracy and efficiency.